Optimal regular reflection of oblique shocks. (October 2019) - Chernyshov, M.V.; Tolpegin, O.A.
Abstract: The regular reflection of oblique steady and unsteady shocks in a perfect gas is considered. Non-monotonic variation of the mechanical and thermal loads on the obstacle with respect to shock/blast wave incidence angle is shown; the obstacle slope angles that correspond to pressure and temperature minima downwards of both steady and unsteady shock reflection point are determined analytically. Achieved minimization of dynamical and thermal loads at shock/blast wave reflection can be of use in space flight safety problems as blast safety onboard a spaceship, protection of spaceport facilities from blast of rocket carrier, prevention of fire onboard, and stable functioning of rocket engines, including ones based on detonation effects. Highlights: Regular reflection of steady and unsteady shocks is studied analytically. General criteria of pressure and temperature extremums are derived. Dynamic and thermal loads in shock reflection were optimized. Damage in emergencies onboard space vehicle and outside it was minimized.